The Functions of Assessment: A Re-Examination - Jeffrey W Barnes (Legal Education Review)
In the 1970s assessment, and examinations in particular, were the focus of world-wide university student protest. In Australian tertiary institutions, greater use was consequently made of “continuous assessment”. After a period of quietude assessment re-emerged a decade later as a “hot” national issue in North America and as the subject of research and discussion in England. In Australia, a report for the Commonwealth Tertiary Education Commission published in 1987 (the “Pearce Report”), discussed at length the question of assessment in Australian law schools. These more recent debates reflected in part the fact that assessment practices in at least the law schools of Australian universities had not fundamentally changed since the seventies revolt. While assessment modes had in the meantime diversified greatly, according to the Pearce Report the problem-type, written examination remained the dominant mode in Australian law schools. In the early 1990s) universities are undergoing a period of rapid change spurred on by Federal government initiatives. One important consequence of this re-evaluation is the affirmation that teaching is the university’s primary function. It is with this ultimate goal in mind that this article is written. The basic premise is that assessment not only serves as a means of certification. It also performs, inevitably, an important teaching function. It is submitted that assessment still suffers from being the “grand afterthought of the educational process”. As is commonly observed, law teachers tend to repeat the methods of instruction that are familiar to them from their student days. In one study most academics surveyed saw assessment only in terms of it providing an incentive to make students work, and to enable their intellectual abilities to be measured. Students (including law students) in another study also viewed it in similar terms. Surveys conducted by the Pearce Inquiry reported widespread dissatisfaction with methods of assessment. Why assessment has been ignored from an educational viewpoint is a complex question. Possible explanations include the influence of the legal profession on teaching; teacher apathy; few incentives; external constraints (such as scarce resources) and the lack of training in and knowledge of educational theory. There is not space to analyse all of these causes. This article’s main concern is more elementary — to remedy the lack of scrutiny of law school assessment as an educational tool. Assessment needs to be re-examined in the light of its teaching and certification functions, but especially the former. To understand what we do or fail to do when we implement assessment schemes, it firstly elaborates on the teaching and certification functions which may be fulfilled and are inevitably fulfilled by student assessment. Current assessment practices are then subjected to a critical analysis. The article concludes by providing a check-list of considerations for the thoughtful law assessor: considerations which, it is submitted, should form the basis of assessment practice.